PENGUATAN PENDIDIKAN KARAKTER MELALUI VALUE BASED TRAINING BAGI PESERTA DIDIK DI SDN 2 JEHEM BANGLI - Ni Made Verayanti Utami; Ni Wayan Suastini; Desak Putu Eka Pratiwi; Ida Bagus Gde Nova Winarta; I Wayan Juniartha (Fakultas Bahasa Asing, 2025)
This community service activity was carried out with the aim of strengthening the character education of students through a collaborative approach.Value Based Training at SDN 2 Jehem Bangli. The background of this program is based on the importance of instilling positive values ​​from an early age, such as discipline, responsibility, cooperation, and honesty, which are the foundation for character building for the younger generation. The implementation method of the activity is carried out through stages of socialization, interactive training, group discussions, and practical application of values ​​in students' daily activities. The participants were students in grades IV–VI of SDN 2 Jehem Bangli who were actively involved in the entire training series. The results of the implementation show an increase in students' understanding of the importance of character values ​​and their ability to internalize these values ​​in their daily behavior, both at school and in the family environment. Thus, the programValue Based Training proven effective as an effort to strengthen character education, as well as being a model of activity that can be implemented sustainably in elementary schools.